Novel 3D scaffolds of chitosan-PLLA blends for tissue engineering applications : preparation and characterization - Duarte, Ana Rita C. (2010)
This work addresses the preparation of 3D porous scaffolds of blends of chitosan and poly(l-lactic acid), CHT and PLLA, using supercritical fluid technology. Supercritical assisted phase-inversion was used to prepare scaffolds for tissue engineering purposes. The physicochemical and biological properties of chitosan make it an excellent material for the preparation of drug delivery systems and for the development of new biomedical applications in many fields from skin to bone or cartilage regeneration. On the other hand, PLLA is a synthetic biodegradable polymer widely used for biomedical applications. Supercritical assisted phase-inversion experiments were carried out in samples with different polymer ratios and different polymer solution concentrations. The effect of CHT:PLLA ratio and polymer concentration and on the morphology and topography of the scaffolds was assessed by SEM and Micro-CT. Infra-red spectroscopic imaging analysis of the scaffolds allowed a better understanding on the distribution of the two polymers within the matrix. This work demonstrates that supercritical fluid technology constitutes a new processing technology, clean and environmentally friendly for the preparation of scaffolds for tissue engineering using these materials.